BK in Double-Membrane Organelles: A Biophysical, Pharmacological, and Functional Survey - González-Sanabria, Naileth; Echeverría, Felipe; Segura, Ignacio; Alvarado-Sánchez, Rosangelina; Latorre, Ramon (Frontiers in Physiology, 2021)
In the 70s, calcium-activated potassium currents were recorded for the first time. In ten years, this Ca2+-activated potassium channel was identified in rat skeletal muscle, chromaffin cells and characterized in skeletal muscle membranes reconstituted in lipid bilayers. This calcium- and voltage-activated potassium channel, dubbed BK for “Big K” due to its large ionic conductance between 130-300 pS in symmetric K+. The BK channel is a tetramer where the pore-forming α subunit contains seven transmembrane segments. It has a modular architecture containing a pore domain with a highly potassium-selective filter, a voltage-sensor domain and two intracellular Ca2+ binding sites in the C-terminus. BK is found in the plasma membrane of different cell types, the inner mitochondrial membrane (mitoBK) and the nuclear envelope’s outer membrane (nBK). Like BK channels in the plasma membrane (pmBK), the open probability of mitoBK and nBK channels are regulated by Ca2+ and voltage and modulated by auxiliary subunits. BK channels share common pharmacology to toxins such as iberiotoxin, charybdotoxin, paxilline, and agonists of the benzimidazole family. However, the precise role of mitoBK and nBK remains largely unknown. To date, mitoBK has been reported to play a role in protecting the heart from ischemic injury. At the same time, pharmacology suggests that nBK has a role in regulating nuclear Ca2+, membrane potential and expression of eNOS. Here, we will discuss at the biophysical level the properties and differences of mitoBK and nBK compared to those of pmBK and their pharmacology and function.